LINKING HOME AND SCHOOL THROUGH MATHEMATICS HOMEWORK; INSIGHTS INTO EFFECTIVE INTERACTIVE MATHEMATICS HOMEWORK DESIGN FOR EARLY LEARNERS - Datius Titus Mutangira; Pambas Basil Tandika; Geraldina Edward (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
The phenomenon that many young learners continue to underperform due to limited home-based support and weak parental involvement though. This study investigates the critical features of effective Interactive Mathematics Homework (IMH) as a strategy to enhance early-grade pupils’ mathematics skills and foster meaningful parental engagement. Employing a qualitative case study design, data were collected through Focused Group Interviews (FGIs) with 63 parents and semi-structured interviews with 21 teachers and 10 head teachers across primary schools in Ukerewe District, Tanzania. Thematic analysis revealed four key characteristics of effective IMH, such ad a manageable number of questions, the inclusion of guided instructions, consistent feedback mechanisms, and alignment with the school curriculum. These elements were found to influence both the usability of the homework for families and its instructional value. The findings suggest that well-designed IMH can bridge the home–school gap in early mathematics education, encouraging collaborative efforts between teachers and parents. The study recommends integrating IMH into early-grade teaching practices to improve pupil outcomes and strengthen family-school partnerships in foundational mathematics learning.